Projection of Climate Impact on Discharge and Energy Production of Cascade Hydroelectric Power Plant in North Sulawesi - Haq, Guntur Ibnu; Hermana, Joni (Research and Social Study Institute, 2025)
Background: Climate change is a major challenge for the sustainability of hydropower plants (PLTA) in tropical areas such as North Sulawesi, which are highly dependent on water availability from seasonal rainfall.Aims & Methods: This study aims to project the water discharge and electricity production of the Tonsealama, Tanggari I, and Tanggari II hydropower plants based on the SSP2-4.5 and SSP5-8.5 climate change scenarios. Historical climate data (2014–2024) from BMKG and hydropower plant operation data (2019–2024) are used to train the prediction model using the Random Forest algorithm, with bias correction performed on the CMIP6 GCM output through a hybrid approach combining Random Forest and Delta Change.Result: The results show a consistent decrease in discharge and energy at the three hydropower plants, especially in May, which has been the peak of the rainy season. The average annual discharge decrease reached 9%, while the decrease in electricity was recorded at 5,528.77 MWh (SSP2-4.5) and 3,053.42 MWh (SSP5-8.5) for the Tonsealama hydropower plant; 8,085.37 MWh and 12,625.98 MWh for PLTA Tanggari I; and the highest decline was experienced by PLTA Tanggari II of 18,160.42 MWh and 9,255.40 MWh. Although higher warming occurs in the SSP5-8.5 scenario, occasional extreme rainfall events partially offset the decline in energy production. These findings emphasize the importance of adaptation strategies through more flexible reservoir management, turbine operations, and integrated water resource planning to increase system resilience to future climate uncertainty.